Regulatory state - Baamonde Gómez, Laura (EUNOMÍA. Revista en Cultura de la Legalidad, 2019)
The aim is to reflect about the concept of regulatory state, and how the role of the state as welfare state has developed in the last decades since the first economic liberalization processes. The crisis of the provider state scheme, has let space for the market private agents in a competition regime. The State, for its part, has reserved for itself the authority of regulator, guarantor and supervisor of the efficient functioning of markets that demand more intensive public intervention for the collective needs satisfaction. Within this framework, this article will also address how this new situation has impacted on the traditional division of powers: role of independent authorities, emergence of new regulatory powers and difficulties for judicial review of the decisions of regulatory agencies. Finally, some lines of action for the future will be proposed.
Keywords: regulatory state; welfare state; regulation; liberalization; competition law; service of general economic interest; independent authorities; self-regulation